Kesantunan Berbahasa Pramuniaga dalam Melayani Konsumen di Toko Buku Sari Anggrek Padang - Sulastutik, Sulastutik; Amir, Amril; Ratna, Ellya (Universitas Negeri Padang, 2013)
This study aims to (1) describe the types of speech acts courtesy clerk in serving consumers when buying and selling bertansaksi Bookstore Sari Orchids in Padang. (2) identify the principles of politeness used salesclerk in serving consumers based on linguistic politeness. This research is a qualitative study using descriptive because this study aimed to describe the data obtained from the field or informants. The data captured on the